Indian River, Portsmouth, Dominica, W.I - Anjo, Jose (My University, 2020)
The postcard depicts the Indian River in Dominica. This is the widest river in Dominica and it flows to the Caribbean Sea between the town of Portsmouth and the village of Glanvillia. It is also the river where some of the scenes from Pirates of the Caribbean were filmed. The postcard is showing the river surrounded by trees and a view of mountains behind. Also, two men can be seen in a boat transporting a horse across the river. Jose Anjo. Photographer, Antigua. YP £12 Info. At the back of card: “Dominica. Leeward Islands. The address only to be written on this side.”
Landscape, black & white,undivided back, 4 x 6 in.
Keywords: People; Trees; Mountains; Rivers; Boats; Horses